Adaptations to isolated shoulder fatigue during simulated repetitive work. Part I: Fatigue. (August 2016) - Tse, Calvin T.F.; McDonald, Alison C.; Keir, Peter J.
Abstract: Upper extremity muscle fatigue is challenging to identify during industrial tasks and places changing demands on the shoulder complex that are not fully understood. The purpose of this investigation was to examine adaptation strategies in response to isolated anterior deltoid muscle fatigue while performing simulated repetitive work. Participants completed two blocks of simulated repetitive work separated by an anterior deltoid fatigue protocol; the first block had 20 work cycles and the post-fatigue block had 60 cycles. Each work cycle was 60 s in duration and included 4 tasks: handle pull, cap rotation, drill press and handle push. Surface EMG of 14 muscles and upper body kinematics were recorded. Immediately following fatigue, glenohumeral flexion strength was reduced, rating of perceived exertion scores increased and signs of muscle fatigue (increased EMG amplitude, decreased EMG frequency) were present in anterior and posterior deltoids, latissimus dorsi and serratus anterior. Along with other kinematic and muscle activity changes, scapular reorientation occurred in all of the simulated tasks and generally served to increase the width of the subacromial space. These findings suggest that immediately following fatigue people adapt by repositioning joints to maintain task performance and may also prioritize maintaining subacromial space width.